Steady state boiling crisis in a helium vertically heated natural circulation loop – Part 2: Friction pressure drop lessening. (January 2016) - Furci, H.; Baudouy, B.; Four, A.; Meuris, C.
Highlights: Experiments were conducted on a 4.2 K boiling helium natural circulation loop. Mass flow rate and pressure drop were measured simultaneously to boiling crisis development. A significant lessening of wall shear stress is caused by the onset of boiling crisis. A practical model was proposed to estimate friction head loss during film boiling. Abstract: Experiments were conducted on a 2-m high two-phase helium natural circulation loop operating at 4.2 K and 1 atm. Two heated sections with different internal diameter (10 and 6 mm) were tested. The power applied on the heated section wall was controlled in increasing and decreasing sequences, and temperature along the section, mass flow rate and pressure drop evolutions were registered. The post-CHF regime was studied watching simultaneously the evolution of boiling crisis onset along the test section and the evolution of pressure drop and mass flow rate. A significant lessening of friction was observed simultaneous to the development of the post-CHF regime, accompanied by a mass flow rate increase, which lets suppose that the vapor film in the film boiling regime acts as a lubricant. A model was created based on this idea and on heat transfer considerations. The predictions by this model are satisfactory for the low quality post-CHF regime.